PENGARUH FINANCIAL LEVERAGE DAN FAKTOR LAINNYA TERHADAP MANAJEMEN LABA - Shania Angella; Yoseph Anastasius Didik Cahyanto (E-Jurnal Akuntansi TSM, 2022)
This research aims to obtain empirical evidence that financial leverage and other factors affect earnings management. Other factors in question are return on assets, firm size, sales growth, managerial ownership, institutional ownership, board size, audit committee, audit quality, and firm age. The population used in this research are non-financial companies listed in Indonesia Stock Exchange (IDX) with a research period from 2018 to 2020, where there are total 104 companies were successfully selected as research samples. The sample selection method used in this research is purposive sampling method while the data analysis method is using multiple regression method. The result of this research shows that audit quality has effect on earnings management, so the better audit quality, the better detection of earnings management practices and there will be minimal earnings management practices. Meanwhile, financial leverage, return on assets, firm size, sales growth, managerial ownership, institutional ownership, board size, audit committee, and firm age have no effect on earnings management, so they will not have any effect on earnings management practices